Steroid Treatment in Macular Edema: A Bibliometric Study and Visualization Analysis - Lin, Yu; Ren, Xiang; Chen, Danian (Frontiers in Pharmacology, 2022)
The use of steroids to treat macular edema (ME) is a research hotspot in ophthalmology. We utilized CiteSpace and VOSviewer software to evaluate the Web of Science Core Collection publications and to build visualizing maps to describe the research progress in this topic. There were 3,252 publications for three decades during 1988–2021. The number of studies was low during the first 14 years but has risen consistently in the following two decades. The average publications per year were only 4.8 during 1988–2002, which jumped to 113 per year during 2003–2012, and 227 per year during 2013–2021. These publications came from 83 countries/regions, with the United States, Germany, and Italy leading positions. Most studies were published in Investigative Ophthalmology Visual Science, and Ophthalmology was the most cited journal. We found 9,993 authors, with Bandello F having the most publications and Jonas JB being the most frequently co-cited. According to our research, the most popular keyword is triamcinolone acetonide (TA). Macular edema, diabetic macular edema (DME), retinal vein occlusion (RVO), dexamethasone (DEX), fluocinolone acetonide (FA), and some other keywords were commonly studied in this field. In conclusion, the bibliometric analysis provides a comprehensive overview of steroid hotspots and developmental tendencies in the macular edema study. While anti-VEGF therapy is the first-line treatment for DME and RVO-induced macular edema, steroids implant is a valid option for these DME patients not responding to anti-VEGF therapy and non-DME patients with macular edema. Combined therapy with anti-VEGF and steroid agents is vital for future research.